Serotonin in the rat prefrontal cortex controls the micturition reflex through 5‐hydroxytryptamine 2A and 5‐hydroxytryptamine 7 receptors. (12th June 2020) - Chiba, Hiroki; Kitta, Takeya; Ohmura, Yu; Higuchi, Madoka; Kon, Masafumi; Nakamura, Michiko; Yoshioka, Mitsuhiro; Shinohara, Nobuo
Abstract : Objectives: To identify the types of serotonin (5‐hydroxytryptamine) receptors of the prefrontal cortex related to the micturition reflex. Methods: Female Sprague–Dawley rats and a microinjection method were used for this study. Stainless steel guide cannulas were implanted bilaterally into the prefrontal cortex, and a polyethylene catheter was inserted into the bladder. Cystometric parameters (intercontraction interval and maximum voiding pressure) were measured before and after injection of any one of six specific antagonists of 5‐hydroxytriptamine receptors (5‐hydroxytryptamine 1A, 5‐hydroxytryptamine 2A, 5‐hydroxytryptamine 2C, 5‐hydroxytryptamine 3, 5‐hydroxytryptamine 4 and 5‐hydroxytryptamine 7) into the prefrontal cortex. The prefrontal cortex was divided into two regions, namely the prelimbic cortex and the infralimbic cortex. The experiments were carried out in conscious and free‐moving rats. Results: The intercontraction interval value increased significantly after injection of the 5‐hydroxytriptamine 2A receptor antagonist, MDL11939, into the prelimbic cortex of the rat prefrontal cortex (7.68 ± 1.28 vs 9.02 ± 1.41 min, P < 0.05), whereas the intercontraction interval value decreased significantly after injection of the 5‐hydroxytriptamine 7 antagonist SB269970 into the prelimbic cortex (9.42 ± 0.39 vs 8.14 ± 0.71 min, P < 0.05). The intercontraction interval was unaffected by injection of either of these two antagonists into the infralimbic cortex. The other four antagonists (5‐hydroxytryptamine 1A, 5‐hydroxytryptamine 2C, 5‐hydroxytryptamine 3 and 5‐hydroxytryptamine 4) had no effect on the intercontraction interval after injection into the prelimbic cortex and the infralimbic cortex. The maximum voiding pressure was unaffected by injection of any one of the six 5‐hydroxytriptamine antagonists into the prelimbic cortex and infralimbic cortex. Conclusions: In the rat prefrontal cortex5‐hydroxytryptamine 2A receptors excite the micturition reflex, whereas 5‐hydroxytryptamine 7 receptors inhibit this reflex.